Design of UWB bidirectional rectangular ring antenna fed by stepped monopole - Lamultree, Suthasinee; Phongcharoenpanich, Chuwong; Torrungrueng, Danai (My University, 2007)
An ultra-wideband rectangular ring antenna led by stepped monopole is presented in this paper. The initial parameters of antenna design as well as the antenna revolutions for enhancing impedance bandwidth are shown. Simulations have been carried out to investigate the impedance and radiation behaviors. It is found that the antenna offers a bidirectional radiation pattern with the impedance bandwidth covered the frequency range from 3.1-10.6 GHz with the VSWR of less than 2:1.
Keywords: Rectangular ring antenna; Stepped monopole; Ultra-wideband